A new tropical species of Aphyllon (Orobanchaceae: Orobancheae) from Chiapas, Mexico - Antonio Francisco-Gutiérrez; Leonardo O. Alvarado-Cárdenas (Botan‪ical Sciences, 2023)
Background: Aphyllon is a genus of 25 root-holoparasitic species restricted to the Americas. It has a disjunct distribution, with 21 species distributed in North America and four in South America. Aphyllon is divided into two sections: Aphyllonand Nothaphyllon. All species of the genus  have host-specificity, make it a study model in the evolution of holoparasitic plants. Recently, observations of a putative new species of Aphyllon were detected on iNaturalist.